Local Wisdom-Based Educational Tourism Model for Children's Science Learning - Wicaksana, Ervan Johan; Rosyadi, Akhmad Fikri; Hasni, Uswatul; Amanda, Rizki Surya (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Science learning is one of the cognitive aspects of children's stimulation in early childhood education. However, science learning practices are rarely carried out in schools due to various factors, including the priority of reading, writing, and arithmetic learning, which is more emphasized so that teachers are less motivated to carry out science activities. Based on this, this study aims to develop an educational tourism model based on local wisdom as a source of children's science learning. This study uses research and development (R&D) with the ADDIE model. The subjects in this study were two experts (material experts and media experts). The trial subjects were 12 students aged 5-6 years. The methods used to collect data were interviews, open questionnaires, and observations. The instruments used to collect data were questionnaires. The techniques used to analyze data were qualitative descriptive analysis, quantitative analysis, and inferential statistics. The study's results, namely testing by two experts, concluded that the educational tourism model was included in the feasible category. Based on the hypothesis test results, it was found that the educational tourism learning model influenced the science abilities of children aged 5-6 years. It was concluded that the educational tourism model based on local wisdom can improve the science abilities of children aged 5-6 years. The implication of this research is that the educational tourism model based on local wisdom can be used as a source of science learning for children.